2010
DOI: 10.1159/000319412
|View full text |Cite
|
Sign up to set email alerts
|

Indications for Endoscopic or Surgical Treatment of Chronic Pancreatitis

Abstract: In patients suffering from chronic pancreatitis, pain as the predominant symptom remains a therapeutic challenge which often cannot be tackled conservatively. Since pancreatic duct obstruction – frequently within the pancreatic head – is an important etiological factor, treatment in these cases aims at decompressing the duct either endoscopically or surgically. Endoscopic drainage includes sphincterotomy, dilation of strictures, removal of stones, and insertion of a stent; it has a success rate of 30–100%. Sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…In patients with a focal CP in the corpus of the pancreas, a middle segmental pancreatic resection has been developed as another organ-preserving operation [ 15 ]. Depending on pathology and location, other procedures include pancreatic left resection or total pancreatectomy [ 16 ].…”
Section: Surgical Techniques For Painful Cpmentioning
confidence: 99%
“…In patients with a focal CP in the corpus of the pancreas, a middle segmental pancreatic resection has been developed as another organ-preserving operation [ 15 ]. Depending on pathology and location, other procedures include pancreatic left resection or total pancreatectomy [ 16 ].…”
Section: Surgical Techniques For Painful Cpmentioning
confidence: 99%
“…In patients with CP refractory to conservative medical treatment, surgery rather than endotherapy is the standard of care. Parenchyma-preserving resections should preferably be performed because they ensure lower morbidity and mortality, preserve endocrine function, and improve quality of life [42]. In a randomized controlled trial, the Berne technique was found to be technically simpler compared with the original Beger's procedure, reflected in significantly shorter operation times and hospital stays.…”
Section: Pain As Indication Of Surgerymentioning
confidence: 99%